2020
DOI: 10.1111/hex.13071
|View full text |Cite
|
Sign up to set email alerts
|

Training in health coaching skills for health professionals who work with people with progressive neurological conditions: A realist evaluation

Abstract: Background Supporting people to self‐manage their long‐term conditions is a UK policy priority. Health coaching is one approach health professionals can use to provide such support. There has been little research done on how to train clinicians in health coaching or how to target training to settings where it may be most effective. Objective To develop theories to describe how training health professionals in health coaching works, for whom and in what circumstances, with a focus on those working with people w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…10 HCP's treating people with progressive neurological conditions in England conveyed that training in health coaching methods was useful; however, it was difficult to fully embrace the coaching role in settings where their clinical experience was more highly valued. 11 This aligns with other studies reporting difficulties for HCP in moving out of their professional disease-focused treatment perspective towards emphasising the person's lived experiences of illness and utilising personal resources for health. 12 Alvarez et al 13 found that levels of patient activation were positively correlated with clinicians' assessment regarding the patients' role in self-management.…”
Section: Introductionsupporting
confidence: 80%
“…10 HCP's treating people with progressive neurological conditions in England conveyed that training in health coaching methods was useful; however, it was difficult to fully embrace the coaching role in settings where their clinical experience was more highly valued. 11 This aligns with other studies reporting difficulties for HCP in moving out of their professional disease-focused treatment perspective towards emphasising the person's lived experiences of illness and utilising personal resources for health. 12 Alvarez et al 13 found that levels of patient activation were positively correlated with clinicians' assessment regarding the patients' role in self-management.…”
Section: Introductionsupporting
confidence: 80%
“…However, we found a wider variety of mechanisms in our evaluation than previously identified, 9 including those relating to pedagogy (i.e., peer learning, didactic teaching), workshop (i.e., duration, content relevance), and individuals (i.e., facilitator competence). Although some of these have been found in previous realist evaluations of faculty development (e.g., interventions employing participatory approaches including reflective practice, having content relevant to faculty needs), 11,15–17 these were previously identified as contexts, not mechanisms. Furthermore, we also identified novel negative mechanisms (e.g., suboptimal peer learning, content irrelevance, suboptimal facilitator competence), extending previous faculty development realist evaluations focusing exclusively on positive mechanisms.…”
Section: Discussionmentioning
confidence: 98%
“… 13 That 2 mechanisms, peer learning and didactic teaching, were most likely triggered in the health care sector, and 2, suboptimal workshop duration and content irrelevance to workplace, in human services, probably reflects differences in supervision cultures, training, and practices across different sectors. 11 , 48 For example, in health care contexts, individuals may prefer peer learning and didactic teaching. In human services contexts, individuals may prefer longer training targeted to their sector (the workshops were mostly underpinned by health literature).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Davies and colleagues used a realist approach to better understand how training health coaches to support those living with long‐term conditions works best, for whom and under what circumstances. After interviewing twenty health‐care professionals and two coaches, the authors concluded that growth in coaches’ confidence required ‘outside the box’ discussion regarding barriers to implementation in practice, and how existing teamwork structures and processes may influence the relevance with which coaching trainees view their training, including use of peer support and ongoing reflection about the training process 15 …”
mentioning
confidence: 99%